2023
DOI: 10.1182/blood.2022017948
|View full text |Cite
|
Sign up to set email alerts
|

IL7-receptor expression is frequent in T-cell acute lymphoblastic leukemia and predicts sensitivity to JAK-inhibition

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematological malignancy with a dismal prognosis related to refractory/relapsing diseases, raising the need for new targeted-therapies. Activating mutations of the IL7-receptor pathway genes (IL7Rp) play a proven leukemia-supportive role in T-ALL. JAK-inhibitors such as ruxolitinib have recently demonstrated preclinical efficacy. However, prediction markers for sensitivity to JAK-inhibitors are still lacking. Herein, we show that IL7R (CD127) express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 34 Numerous recent studies show the IL-7R pathway to be critical for ALL development 5 , 6 , 10 , 35 , 36 and its exploitability for ALL treatment. 12 , 13 , 14 , 37 , 38 Preclinical data suggest that direct targeting of IL-7R in ALL cells using research-grade CD12 mAbs outperforms inhibitors of IL-7R downstream effectors such as ruxolitinib (targeting JAK/STAT signaling). 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 Numerous recent studies show the IL-7R pathway to be critical for ALL development 5 , 6 , 10 , 35 , 36 and its exploitability for ALL treatment. 12 , 13 , 14 , 37 , 38 Preclinical data suggest that direct targeting of IL-7R in ALL cells using research-grade CD12 mAbs outperforms inhibitors of IL-7R downstream effectors such as ruxolitinib (targeting JAK/STAT signaling). 12 …”
Section: Discussionmentioning
confidence: 99%
“… 48 Additionally, a recent report showed comparable expression levels of CD127 in pediatric and adult patients, suggesting that both groups may benefit from IL-7R immunotherapy. 38 …”
Section: Discussionmentioning
confidence: 99%
“…One study found that IL-7 was able to increase the number of CD4+ and CD8+ T cells and improve the function of these cells in lymphoma patients. The combination of IL-7 with chemotherapy or immunotherapy has been suggested as a potential therapeutic strategy for improving the treatment response and survival in lymphoma patients [ 91 ]. IL-7 has also shown potential in the treatment of colorectal cancer.…”
Section: Il-7 In Tumour Therapymentioning
confidence: 99%
“…T-cell acute lymphoblastic leukemia (T-ALL) is a highly aggressive and heterogeneous hematological malignancy of T-cell progenitors that is associated with a high relapse rate and mortality. , Intensive chemotherapy, as the standard and first-line treatment, has substantially improved the survival outcomes of T-ALL patients who can tolerate it. However, the clinical prognosis of frail patients intolerant to chemotherapeutics and relapsed patients resistant to chemotherapy remains poor as a result of the severe lack of therapeutic options. Nelarabine, the only drug approved for treating relapsed and refractory T-ALL patients, only achieved a one-year overall survival of ca. 24% and carried a boxed warning for severe neurotoxicity. Therefore, there is a desperate need to develop effective and safe therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…T-cell acute lymphoblastic leukemia (T-ALL) is a highly aggressive and heterogeneous hematological malignancy of Tcell progenitors that is associated with a high relapse rate and mortality. 1,2 Intensive chemotherapy, as the standard and firstline treatment, has substantially improved the survival outcomes of T-ALL patients who can tolerate it. 3−5 However, the clinical prognosis of frail patients intolerant to chemotherapeutics and relapsed patients resistant to chemotherapy remains poor as a result of the severe lack of therapeutic options.…”
Section: Introductionmentioning
confidence: 99%